Pengaruh Metode Pembelajaran Course Review Horay Berbantuan Media Question Card Terhadap Keaktifan Belajar Peserta Didik - Asnur, Latifah; Kustati, Martin; Amelia, Rezki (Edudeena : Journal of Islamic Religious Education, 2024)
Abstract: The aim of this research is to see whether there is an influence of the Course Review Horay method assisted by Question Card Media on students' learning activity. The True Experimental Design research type is the strongest type of research because in this design the researcher can control all external variables that influence the course of the experiment. The results of this research showed that the learning activity in the control class which used the conventional model after the post-test was carried out was an average of 74.56. In the experimental class, learning activity using the Course Review Horay learning method assisted by Question Card media after the post-test was carried out, obtained an average of 89.7. Based on the hypothesis test, significance = 0.001, meaning sig = 0.001 < 0.05, then H_0 is rejected, H_a is accepted. This means that there is an influence of the Course Review Horay learning method assisted by Question Card media on the active learning of MTsS TI Batang Kabung students. This is shown by indicators of students who have a good interaction process, namely actively asking questions, actively providing responses, actively conveying ideas and actively providing confirmation of understanding. This is influenced by the teacher's teaching style, class atmosphere, student characteristics and learning materials. Abstrak: Tujuan penelitian ini untuk melihat apakah ada pengaruh metode Course Review Horay berbantuan Media Question Card terhadap Keaktifan Belajar Peserta Didik. Jenis penelitian True Experimental Design, merupakan jenis penelitian yang paling kuat karena dalam desain ini peneliti dapat mengontrol semua variabel luar yang memperngaruhi jalannya eksperimen. Hasil penelitian ini didapatkan bahwa keaktifan belajar pada kelas kontrol yang menggunakan model konvensional setelah dilakukan post-test diperoleh rata-rata sebesar 74,56. Pada kelas eksperimen keaktifan belajar dengan menggunakan metode pembelajaran Course Review Horay berbantuan media Question Card setelah dilakukan post-test diperoleh rata-ratasebesar 89,7. Berdasarkan uji hipotesis diperoleh signifikansi = 0,001, artinya sig = 0,001< 0,05, maka H0 ditolak Ha diterima. Artinya terdapat pengaruh metode pembelajaran Course Review Horay berbantuan media Question Card terhadap keaktifan belajar peserta didik MTsS TI Batang Kabung. Hal ini ditunjukkan dengan indikator siswa yang memiliki proses interaksi yang baik, yakni aktif bertanya, aktif memberikan tanggapan, aktif menyampaikan ide dan aktif dalam memberikan konfirmasi pemahaman. Hal ini dipengaruhi oleh gaya mengajar guru, suasana kelas, karakteristik siswa dan materi pembelajaran.